Applications of Plant Metabolic Engineering - Verpoorte, R.; Alfermann, A.W.; Johnson, T.S.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Written by leading international experts in the field of plant metabolic engineering, this book discusses, mainly, applications of plant metabolic engineering. Metabolic engineering, which is part of second generation biotechnology, has made several contributions at basic level as well as at conceptualising products ever since its emergence in the early 1980s. Applications resulting from metabolic engineering are expected to play a very important role in future for plant breeding, e.g. for improved resistance or improved traits concerning health promoting constituents, and production of fine chemicals such as medicines, flavors and fragrances. Considering the tremendous progress that has been made since our first book in the year 2000 urgency was felt to bring together cutting edge research in plant metabolic engineering in applied aspects as a handy reference book. This book has been predominantly dedicated to applied research of metabolic engineering, and a part of it has been allotted for fundamental research that has potential applications. This book is a unique source of information for all those involved with plants as chemical factories of fine chemicals and also to more experienced scientists who work on transgenic plants, besides, senior researchers, graduate students, post-doctroral students, teachers and students as well.
Biosynthesis of Plant Natural Products and Characterization of Plant Biosynthetic Pathways in Recombinant Microorganisms -- Plant Molecular Farming: Host Systems, Technology and Products -- Plastid Pathways -- Metabolic Engineering of the Alkaloid Biosynthesis in Plants: Functional Genomics Approaches -- Polyamine Biosynthetic Pathway: A Potential Target for Enhancing Alkaloid Production -- Metabolic Engineering in Alkaloid Biosynthesis: Case Studies in Tyrosine- and Putrescine-Derived Alkaloids -- Application of Metabolic Engineering to Vanillin Biosynthetic Pathways in Vanilla Planifolia -- Pathway Engineering of the Plant Vitamin C Metabolic Network -- Metabolic Engineering of Terpenoid Biosynthesis in Plants -- Metabolic Engineering of Seed Oil Biosynthetic Pathways for Human Health -- Metabolic Engineering in Sugarcane: Assisting the Transition to a Bio-based Economy -- Single-chain Fv Antibody Stimulates Biosynthesis of Secondary Metabolites in Plants -- Metabolic Engineering of Sulfur Assimilation in Plants -- Approaches to Quality Plant Based Medicine: Significance of Chemical Profiling.
Keywords: LIFE SCIENCES; CHEMISTRY; BIOTECHNOLOGY; GENETIC ENGINEERING; AGRICULTURE; BIOCHEMISTRY; BOTANY; LIFE SCIENCES; PLANT SCIENCES; PLANT BIOCHEMISTRY; AGRICULTURE; CHEMISTRY/FOOD SCIENCE, GENERAL; GENETIC ENGINEERING; BIOTECHNOLOGY